Language, Mobility and Employability among Southeast Asian Migrant Workers in Japan. Issue 4 (2nd October 2022) - Hashimoto, Kayoko
ABSTRACT: There have been widespread concerns about the decline of modern languages and the waning interest in learning languages other than English around the world. The Association of Southeast Asian Nations officially adopted English as its working language in 2008, in stark contrast to the European Union, which has 24 official languages. This decision has changed the nature of multilingualism in the region, but its impact on other foreign languages is largely unknown. In recent decades, Japan, which has not exercised economic and cultural influence in Southeast Asia through its language, has increasingly relied on foreign labour due to its declining population. On the one hand, this has encouraged transnational migration between Southeast Asia and Japan as well as a Japanese language boom for work purposes, but on the other, it has exposed Japan's reluctance to change its immigration policy and its indifference to taking responsibility for the language learning of foreign residents in Japan. This cross-disciplinary Special Issue offers diverse perspectives on Japanese language teaching and learning in relation to mobility and employability. Bringing them together in one issue presents a more rounded picture of Japan's instrumental approach to developing the language skills of workers from Southeast Asia.